Effect of Foot Reflexology and Gentle Stretching Exercises on Pain Intensity in Patients after Spine Surgery: A Randomized Controlled Trial - Mahmoud Bakhshi; Hossein Ranjbar; Ommolbanin Rostami; Hamid Chamanzari; Hamidreza Bahrami-Taghanaki (Journal of Evidence-Based Care, 2022)
Background: The side effects of long-term use and high doses of drugs have increased the use of complementary therapies for the reduction of pain.Aim: The present study aimed to compare the effect of foot reflexology and gentle stretching exercises on pain intensity in patients after spine surgery.Method: This clinical trial study was performed on 90 patients undergoing spinal surgery referring to hospitals affiliated to Mashhad University of Medical Sciences in 2019. Patients were randomly assigned to three groups: foot reflexology, gentle stretching exercises, and control. In intervention groups, apart from the routine procedures, foot reflexology or gentle stretching exercises were performed daily from the first day after surgery until discharge, and also three times a week for six weeks after discharge. In the control group, only routine care was performed.Results: The mean age of the samples was 43.35±11.15 years. In within-group comparison, the mean pain intensity was significantly decreased at the end of the sixth week after surgery in all three groups (P<0.001). The mean of pain intensity in the reflexology group was lower than that in the stretching exercise group on the second day after surgery, discharge time, as well as the first and sixth weeks after discharge (P<0.001). Nonetheless, there was no significant difference between the stretching exercise group and the control group (P<0.05).Implications for Practice: Foot reflexology effectively reduces the pain intensity of patients after spinal surgery. Therefore, it is recommended to be performed by patients or their caregivers to reduce pain after spinal surgery.